Identification of Diversity Bonorowo Aquatic Fish Species in Kalitengah Subregency, Lamongan Regency - Endah Sih Prihatini; Suyoto Suyoto; Fuquh Shaleh (Indonesian Journal of Limnology, 2023)
Lamongan regency  is one of the areas in the Bengawan Solo watershed always overflow during rainy period and around 50.17 percent of the area was a flood-stricken area called bonorowo. This study aims to identify the composition, species diversity, and potential of fish resources found in the waters of Bonorowo, Kalitengah, Lamongan for 3 months from July to September 2022. The research method is purposive random sampling method. Fish samples were taken using five types of fishing gear, namely gill nets, nets, fishing rods, bubu, and strums. Data was analysed by using relative abundance of each type of fish, frequency of occurrence, the diversity index, evennes index. Also, water quality measurements was done in situ include pH, transparency, temperature, and DO. The results of research showed that there were 16 species which belong to 10 families (Cyprinidae, Channidae, Cichlidae, Claridae, Loricariidae, Belontiidae, Anabantidae, Bagridae, Synbranchidae and Macrobrachium). The structure of the fish community is as follows: the composition of the fish species with the highest percentage of relative abundance is the family Cichlidae represented by species Oreochrosmis mossambicus (18,45%), while catfish (Clarias sp) has the lowest percentage at 1.39%. The diversity index range from 2,493 – 2,540 in the medium category, the evennes index ranges from 0.395 – 0.414 in the medium category, so it is quite uniform, and the all-round dominance index is in the low category for all stations because it ranges from 0.093 to 0.104. For potential analysis, there are two types of fish that have the potential to become ornamental fish, namely Channa striata and Trichogaster trichopterus. As well as the results of measuring water quality parameters prove that the condition of bonorowo waters in Kalitengah sub-regency is good for fish life.